PCR Primer Design - Basu, Chhandak.; Basu, Chhandak. (Methods in Molecular Biology, 2015)
This volume provides an overview on design PCR primers for successful DNA amplification. Chapters focus on primer design strategies for quantitative PCR, in silico PCR primer design , and primer design using software. Written in the highly successful Methods in Molecular Biology  series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, PCR Primer Design, Second Edition seeks to aid molecular biology students, researchers, professors and PCR enthusiasts.